Synthesis of 2,4,6-Triarylpyridines Using ZrOCl2 under Solvent-Free Conditions - Moosavi-Zare, Ahmad Reza; Zolfigol, Mohammad Ali; Farahmand, Shohreh; Zare, Abdolkarim; Pourali, Ali Reza; Ayazi-Nasrabadi, Roya (Synlett, 2014)
An efficient procedure for the synthesis of 2,4,6-triarylpyridines (Kröhnke pyridines) by the one-pot multicomponent condensation of aldehydes (1 equiv) with acetophenones (2 equiv) and ammonium acetate (1.2 equiv) in the presence of catalytic amounts of oxozirconium(IV) chloride (ZrOCl2) under solvent-free conditions is described. In this work, four products have been reported for the first time. Easy work-up, simple methodology, clean reaction and reusability of the catalyst are some advantages of this work.
Keywords: pyridine; multicomponent reactions; zirconium; Kröhnke pyridine; solvent-free